The Pardisomus species from Costa Rica, with descriptions of four new species and one larva (Coleoptera: Curculionidae: Baridinae). - Prena, Jens (Contributions to Entomology = Beiträge zur Entomologie, 2003)
The neotropical weevil genus Pardisomus Pascoe is redefined based on morphological character states of Agalmatus Kuschel and association of six species with Pentagonia Bentham (Rubiaceae). Procholus Desbrochers, Anambates Casey, Piazambates Voss and Agalmatus are new synonyms of Pardisomus. New combinations with Pardisomus are 1) from Agalmatus: P. brasiliensis (Kuschel), P. geniculatus (Hustache), P. nigritarsis (Kuschel), P. panamensis (Kuschel); 2) from Embates: P. cleroides (Champion); 3) from Lydamis: P. squamipes (Kirsch); 4) from Peridinetus: P. rufescens (Hustache); 5) from Piazambates: P. piazuroides (Voss); and 6) from Procholus: P. biplagiatus (Desbrochers). Four new species of Pardisomus are described from Costa Rica: P. albescens, P. amotus, P. byrrus and P. suffuscus. The larva of putative P. biplagiatus is described for the first time. Keywords weevils, taxonomy, new species, Pentagonia, Neotropics. Nomenclatural Acts Agalmatus Kuschel, 1958 (Curculionidae), syn. n. of Pardisomus Pascoe,1889 Anambates Casey, 1922 (Curculionidae), syn. n. of Pardisomus Pascoe,1889 Procholus Desbrochers, 1907 (Curculionidae), syn. n. of Pardisomus Pascoe,1889 Piazambates Voss, 1954 (Cureculionidae), syn. n. of Pardisomus Pascoe,1889 albescens Prena, 2003 (Pardisomus), spec. n. amotus Prena, 2003 (Pardisomus), spec. n. biplagiatus (Desbrochers, 1906) (Pardisomus), Lectotype; comb. n. hitherto Pseudolochus biplagiatus brasiliensis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus brasiliensis byrrus Prena, 2003 (Pardisomus), spec. n. cleroides (Champion, 1907) (Pardisomus), Lectotype; comb. n. hitherto Ambates cleroides geniculatus (Hustache, 1950) (Pardisomus), comb. n. hitherto Peridinetus geniculatus nigritarsis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus nigritarsis panamensis (Kuschel, 1958) (Pardisomus), comb. n. hitherto Agalmatus panamensis piazuroides (Voss, 1954) (Pardisomus), comb. n. hitherto Piazambates piazuroides rufescens (Hustache, 1950) (Pardisomus), comb. n. hitherto Peridinetus rufescens squamipes (Kirsch, 1857) (Pardisomus), comb. n. hitherto Scambus squamipes suffuscus Prena, 2003 (Pardisomus), spec. n.